Geoscience and Information Technology in the Queensland Department of Resource Industries (The Australasian Institute of Mining and Metallurgy, 1990)
The Department of Resource Industries regulates and oversees safety and environmental standards for the mining and related industries in Queensland, and provides scientific support through its effort in the geosciences.The geoscientific data base accumulated over more than 120 years is very large. Therefore, accessibility to and utilisation of the data base in the most effective manner is an issue to be addressed in terms of modern information technology. The Department has developed a strategy whose implementation is progressing rapidly.